The Strategic Meaning of CBCA Criteria From the Perspective of Deceivers - Maier, Benjamin G.; Niehaus, Susanna; Wachholz, Sina; Volbert, Renate (Frontiers in Psychology, 2018)
In 2014, Volbert and Steller introduced a revised model of Content-Based Criteria Analysis (CBCA) that grouped a modified set of content criteria in closer reference to their assumed latent processes, resulting in three dimensions of memory-related, script-deviant and strategy-based criteria. In this model it is assumed that deceivers try to integrate memory-related criteria – but will not be as good as truth tellers in achieving this – whereas out of strategic considerations they will avoid the expression of the other criteria. The aim of the current study was to test this assumption. A vignette was presented via an online-questionnaire to inquire how participants (n = 135) rate the strategic value of CBCA criteria on a five-point scale. One-sample t-tests showed that participants attribute positive strategic value to most memory-related criteria and negative value to the remaining criteria, except for the criteria self-deprecation and pardoning the perpetrator. Overall, our results corroborated the model’s suitability in distinguishing different groups of criteria – some which liars are inclined to integrate and others which liars intend to avoid - and in this way provide useful hints for forensic practitioners in appraising the criteria’ diagnostic value.